Impact of technology (engineering) on business operations in Nigeria (1960-1998) (2000)
Despite the low-level of Technological inputs and assimilation in Nigeria in general, Business operations have benefited considerably from Technology. Technology input have been in form of vastly improved communications, power availability, distribution, new tools of machinery for production, and health facilities. In this paper, the situation of Transportation and Food industries are focused on in respect of great changes that have taken place therein. Suggestion on the practical way of having greater progress are listed to serve as guides for policy makers in the country.